Characterization and modeling of laser transmission welded polyetherketoneketone (PEKK) joints: Influence of process parameters and annealing on weld properties - Marcela Matus-Aguirre; Benoît Cosson; Christian Garnier; Fabrice Schmidt; André Chateau Akué-Asséko; France Chabert (Journal of Advanced Joining Processes)
Welding high-performance thermoplastics has gained popularity across various industries such as automotive, aerospace, and medical. Laser transmission welding (LTW) has emerged as an effective method for joining thermoplastic parts due to its precise control and high joint quality. PAEK (polyaryletherketone) are wide spreading over various industrial applications as a substitute to metals and thermosets when high durability and performance are required. Polyetherketoneketone (PEKK) is one of these PAEK and it has received less attention than PEEK until now. PEKK, being a semi-crystalline thermoplastic, requires additional care during processing due to its propensity to crystallize. This study presents both experimental and numerical investigations into LTW of PEKK molded parts, aiming to understand the influence of welding parameters and crystallinity on weld joint morphology and mechanical properties. PEKK plates, prepared in amorphous and semi-crystalline states, are subjected to LTW using a 975 nm diode laser. Material characterization confirms differences in crystallinity between the samples, which affect their thermal and optical properties, which are crucial for welding. Welding tests are conducted with varying laser power (between 75 and 95 W) and semi-transparent part thickness (2 and 4 mm). The morphology of joints is analysed. Assemblies undergo post-weld annealing treatment to examine its influence on weld crystallinity and consequent mechanical properties. Results reveal an anisotropic distribution of crystallinity within the heat-affected zone (HAZ). The depths of the molten layer (ML) and semi-crystalline layer (scL) vary with laser power and assembly type. A notable decrease in weld strength with laser power is highlighted, while annealing leads to enhanced crystallinity and improved weld strength. Despite variations, high weld strengths are achieved with annealing. Computational modelling elucidates the complex interplay between laser irradiation, temperature distribution, and crystallization kinetics observed experimentally. Overall, this comprehensive investigation provides valuable insights into optimizing LTW parameters for PEKK parts.